Relationship between Health Locus of Control and Eating Behavior in Diabetics in the Work Area of Health Center Sumbersari - Iqro' Ayatullah, Muhammad; Tri Bagus, Cahya; Andriani, Sri Wahyuni (Universitas Bondowoso, 2024)
ABSTRACT Background: Diabetes mellitus is a complex metabolic disorder characterized by hyperglycemia, a physiological abnormal condition characterized by a continuous increase in blood glucose levels. Health locus of control (HLOC) is a human belief about the location of health control and has a central role in health services. Eating behavior is a broad term that includes food choices and motivations, eating habits, eating patterns, and food-related problems such as obesity, eating disorders, and eating disorders. Method: This study uses a correlational research design with a cross sectional approach, aiming to correlate between health locus of control and eating behavior. The population in this study were diabetics in the working area of the Sumbersari health center with a sample size of 267 respondents. The sampling technique used Simple Random Sampling. The data collection process used multidimensional health locus of control questionnaire and ducth eating behavior questionnaire. Result: The results of research on health locus of control show that the majority of diabetics have sufficient health locus of control. The results of eating behavior research show that the majority of diabetics have moderate eating behavior. The results of the study using the Spearman rho Rank test (α = 0.05) showed a relationship between health locus of control and eating behavior in diabetics in the Sumbersari working area, with a p value = 0.000. Conclusion: The conclusion of this study is that there is a relationship between health locus of control and eating behavior in diabetics. The recommendation of this study is that it can be used as a reference for nurses in conducting education and interventions for diabetics to pay more attention to health locus of control with eating behavior in diabetics.